2009
DOI: 10.5585/conssaude.v8i2.1493
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação do interesse dos pais pela saúde bucal de seus filhos pelo índice de comparecimento às consultas odontológicas de crianças em idade pré-escolar

Abstract: Este estudo teve por objetivo quantificar o índice de comparecimento às consultas odontológicas de crianças entre 4 e 5 anos de idade, frequentadoras de pré-escola, agendadas em um espaço coletivo predeterminado e encaminhadas para uma Unidade Básica de Saúde (UBS) mais próxima de suas residências. Após terem sido examinadas e classificadas, por meio de critérios específicos de risco para a doença cárie, como de alto risco, buscou-se relacionar esse índice obtido com o conhecimento dos pais sobre a prevenção e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 12 publications
0
4
0
1
Order By: Relevance
“…On the other hand, there are studies that verified the depreciation, by caregivers, of the deciduous dentition, predominant in children, due to the fact that it is a temporary tooth [ 26 ]. Corroborating with this last statement, Siqueira et al, [ 2 ] reported, in a research involving 4 and 5-year-old children, the high rate of dental appointments absence (42.4%) and concluded that this fact indicates either the unawareness of the importance of the treatment or health neglect. They also found that most of the absences were by poor families that, even with free treatment, were not interested in attending dental appointments.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…On the other hand, there are studies that verified the depreciation, by caregivers, of the deciduous dentition, predominant in children, due to the fact that it is a temporary tooth [ 26 ]. Corroborating with this last statement, Siqueira et al, [ 2 ] reported, in a research involving 4 and 5-year-old children, the high rate of dental appointments absence (42.4%) and concluded that this fact indicates either the unawareness of the importance of the treatment or health neglect. They also found that most of the absences were by poor families that, even with free treatment, were not interested in attending dental appointments.…”
Section: Discussionmentioning
confidence: 87%
“…However, despite the great advancements in oral health policies, caries disease is still a severe problem that hinders such development [ 2 ]. Among the factors associated with the high prevalence of caries in infants is the lack of caregiver’s care concerning child’s oral health [ 2 , 3 ], which characterizes a neglect act [ 4 ]. Neglect is “a type of maltreatment that refers to the failure by the caregiver to provide needed, age-appropriate care although financially able to do so or offered financial or other means to do so” [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…One study found that the elevated degree of instruction of parents comes with more opportunities to information access on health [22]. Children who live with adults, in this condition, are subject to healthier habits and behaviors of oral health [19].…”
Section: Discussionmentioning
confidence: 99%
“…Results showed that the parents or guardians of these children mostly seem to have adequate behaviors, habits and oral health knowledge, as the parents are the first agents of socialization and they are the ones who promote the basic principles of hygiene and prevention in the children, consequently affecting their oral health. Siqueira et al (2009) [26] evaluated the interest of the parents in their children oral health through the attendance index of dental appointments, concerning preschool children aged 4 to 5 years, referred to a Basic Health Unit near to their homes. Results indicated the absence of information from the parents about the importance and care with oral hygiene, mainly about the primary teeth.…”
Section: Intrauterine Dentistry and Dentistry For Babies | Cazuza And Takahashimentioning
confidence: 99%